Magnetic solid-phase extraction agent based on carbon-coated Fe3O4 as well as preparation method and application of magnetic solid-phase extraction agent

The carbon-coated Fe3O4 magnetic nanoparticles were prepared by a one-step hydrothermal method, and the covalent organic framework materials were fixed through biomassive method and acetal reaction, which solved the problem of cumbersome preparation process and difficulty in modifying covalent organic framework materials in the prior art, and achieved the improvement of the stability and specific surface area of ​​the magnetic solid-phase extractor.

CN119633781APending Publication Date: 2025-03-18TIANJIN UNIV OF TRADITIONAL CHINESE MEDICINE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411597629.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

The existing carbon-coated iron tetraoxide nanoparticles have problems such as cumbersome, uncontrollable thickness of the coating material, low specific surface area, and reduced superparamagnetic properties during the preparation process, and it is difficult to modify the surface of magnetic particles covered with inert materials.

Method used

Carbon-coated Fe3O4 magnetic nanoparticles were prepared by one-step hydrothermal method, and dopamine polymer was coated on the surface of the magnetic nanoparticles by biomimetic method, and then the covalent organic framework material polyDVA-TAPB was fixed by acetal reaction.

Benefits of technology

The stability and specific surface area of ​​magnetic solid-phase extractor are improved, superparamagnetic and biocompatibility are maintained, the extraction process is simplified, and the problem of covalent organic framework materials fixing on the surface of magnetic particles is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119633781A_ABST
    Figure CN119633781A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of new materials, in particular to a magnetic solid-phase extractant based on carbon-coated Fe3O4 and a preparation method and application thereof.The solid-phase extractant comprises a Fe3O4 core, a carbon layer and a covalent organic framework, the carbon layer coats the surface layer of the Fe3O4 core, and the covalent organic framework is fixed to the carbon layer; the surface of the carbon layer is modified with hydroxyl and amino chemical bonding sites, the carbon layer covering the surface can effectively protect the magnetic inner core from being oxidized, the stability of the magnetic material structure is kept, and the agglomeration phenomenon caused by long-time exposure is avoided; the solid-phase extraction agent has good adsorption and enrichment effects on estrogen compounds, and is expected to be used for enrichment and determination of the estrogen compounds in samples such as food and plasma through liquid-phase system analysis; the preparation method of the solid-phase extraction agent is simple and convenient, easy to operate and beneficial to large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of new materials, and in particular to a magnetic solid phase extractant based on carbon-coated Fe3O4, and a preparation method and application thereof. Background Art

[0002] Magnetic Solid Phase Extraction (MSPE) is a dispersed solid phase extraction technology based on magnetic or magnetizable materials as adsorbents. In the MSPE process, the magnetic adsorbent is not directly filled into the adsorption column, but is added to the solution or suspension of the sample. The target analyte is adsorbed to the surface of the dispersed magnetic adsorbent, and then under the action of the external magnetic field, the target analyte migrates with the adsorbent, and finally the measured substance is eluted with a suitable solvent, thereby separating it from the matrix of the sample. MSPE adsorbents are usually composed of magnetic materials and functionalized modified coatings.

[0003] As a common magnetic adsorption material, ferroferric oxide nanoparticles (Fe3O4NPs) often cause agglomeration between nanoparticles due to their high surface energy and van der Waals forces between particles. Moreover, they will corrode and oxidize when exposed to air for a long time, which greatly limits the performance and application scenarios of this magnetic adsorption material. To avoid this phenomenon, carbon-coated ferroferric oxide nanoparticles combine the characteristics of carbon and ferroferric oxide, increasing the dispersibility and stability of magnetic particle materials. However, the currently common carbon-coated ferroferric oxide nanoparticles are usually coated with a carbon layer on the surface of synthesized ferroferric oxide nanoparticles, which has problems such as complicated preparation process, uncontrollable thickness of coating material, low specific surface area, and reduced superparamagnetism.

[0004] Covalent Organic Frameworks (COFs) are a type of "porous" polymer with a large specific surface area, good chemical stability, and high mechanical stability. In particular, its units and skeleton structures can be customized, which makes it show broad application prospects in the fields of adsorption and separation. Under normal circumstances, COFs "grow" on the surface of magnetic materials in a chemically bonded manner, and the target analytical compounds are selectively enriched through MSPE. The inert materials on the surface of carbon-coated ferroferric oxide nanoparticles have a certain resistance to chemical modification and do not have functional groups for chemical bonding. Therefore, COFs are not easy to modify the surface of magnetic particles coated with inert materials and are easy to fall off. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the related art. To this end, the first object of the present invention is to provide a magnetic solid phase extractant based on carbon-coated Fe3O4; the second object of the present invention is to provide a preparation method of the magnetic solid phase extractant; the third object of the present invention is to provide an application of the magnetic solid phase extractant.

[0006] In order to achieve the first purpose, the technical solution adopted by the present invention is: A magnetic solid phase extractant based on carbon-coated Fe3O4, comprising a Fe3O4 core, a carbon layer and a covalent organic skeleton, wherein the carbon layer is coated on the surface of the Fe3O4 core, and the covalent organic skeleton is fixed on the carbon layer; Wherein, the surface of the carbon layer is modified with hydroxyl and amino chemical bonding sites.

[0007] Furthermore, the Fe3O4 core is Fe3O4 magnetic nanoparticles.

[0008] Furthermore, the hydroxyl and amino chemical bonding sites used to modify the surface of the carbon layer are provided by polydopamine modified on the surface of the carbon layer.

[0009] Furthermore, the covalent organic skeleton is an organic skeleton material formed by covalently linking 2,5-divinylterephthalaldehyde (2,5-divinylterephthalaldehyde, referred to as DVA) and 1,3,5-tris(4-aminophenyl)benzene (1,3,5-Tris(4-aminophenyl)benzene, referred to as TAPB).

[0010] In order to achieve the second purpose, the technical solution adopted by the present invention is: A method for preparing a magnetic solid phase extractant, for preparing any of the above-mentioned magnetic solid phase extractants based on carbon-coated Fe3O4, comprising the following steps: S100, using a polyvinyl alcohol solution and an iron salt solution to prepare Fe3O4 magnetic nanoparticles with a carbon layer coated on the surface; S200, using a dopamine solution to modify Fe3O4 magnetic nanoparticles with a carbon layer on the surface to obtain magnetic nanoparticles with polydopamine modified on the surface; S300, placing magnetic nanoparticles modified with polydopamine on the surface into an organic solution of DVA and TAPB, and preparing a magnetic solid phase extractor based on carbon-coated Fe3O4 through an acetal reaction.

[0011] Furthermore, in step S100, the mass concentration of the polyvinyl alcohol solution is 0.2 g / mL to 0.25 g / mL.

[0012] Furthermore, in step S100, the mass concentration ratio of the polyvinyl alcohol solution to the iron salt solution is 1:1 to 1:1.25.

[0013] Furthermore, in step S200, the concentration of the dopamine solution is 1 mg / mL to 2 mg / mL.

[0014] Further, in step S300, the mass ratio of DVA to TAPB is 4:1 to 6:1.

[0015] In order to achieve the third purpose, the technical solution adopted by the present invention is: An application of a magnetic solid phase extractant, wherein the magnetic solid phase extractant is any of the magnetic solid phase extractants based on carbon-coated Fe3O4 as described above, and the application includes being used for the enrichment and analysis of estrogen compounds.

[0016] The above one or more technical solutions in the embodiments of the present invention have at least one of the following technical effects: The present invention provides a magnetic solid phase extractor based on carbon-coated Fe3O4. Compared with the currently commonly used magnetic nanomaterials, the carbon layer coated on the surface can effectively protect the magnetic core from oxidation, maintain the stability of the magnetic material structure, and avoid agglomeration caused by long-term exposure. The magnetic nanoparticles coated with the carbon layer have the advantages of large specific surface area, superparamagnetism, and good biocompatibility. Moreover, the magnetic nanoparticles coated with the carbon layer can be transferred and recovered under the action of an external strong magnet, simplifying the operation steps in the extraction process.

[0017] The present invention provides a method for preparing a magnetic solid-phase extractant, which is easy to operate and has low cost of reagent raw materials. Nano-scale particles with small particle size, uniform size and controllable morphology can be prepared by a one-step hydrothermal method. The magnetic nanoparticles coated with a carbon layer have a certain resistance to chemical modification, and it is difficult to modify the covalent organic framework material on their surface directly by chemical bonding. The present invention uses a biomimetic method to pretreat the magnetic nanoparticles coated with a carbon layer, and coats the dopamine polymer on the surface of the magnetic nanoparticles; then the covalent organic framework material poly DVA -TAPB is fixed by an acetal reaction. The coating of the covalent organic framework material poly DVA -TAPB is uniform and of consistent thickness, and there is no phenomenon of the modification layer falling off after long-term use. The preparation method provided by the present invention solves the problem of fixing a covalent organic framework on the surface of materials such as magnetic nanoparticles coated with a carbon layer that is inert to chemical modification.

[0018] The magnetic solid phase extractant based on carbon-coated Fe3O4 provided by the present invention has good adsorption and enrichment effects on estrogen compounds, and is suitable for enrichment and determination of such substances in samples such as food and plasma through liquid phase system analysis.

[0019] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a scanning electron microscope image of Fe3O4 magnetic nanoparticles coated with a carbon layer provided in Example 1 of the present invention, with a scale of 100 nm.

[0021] Figure 2 This is a scanning electron microscope image of Fe3O4 magnetic nanoparticles coated with a carbon layer provided in Example 1 of the present invention, with a scale of 10 nm.

[0022] Figure 3 This is a scanning electron microscope image of the magnetic solid phase extractor based on carbon-coated Fe3O4 provided in Example 1 of the present invention, with a scale of 10 nm.

[0023] Figure 4 This is a schematic diagram of the process of using the carbon-coated Fe3O4-based magnetic solid phase extraction agent provided in Example 1 of the present invention for the detection of estrogen compounds.

[0024] Figure 5 This is a high performance liquid chromatogram of the magnetic solid phase extractor based on carbon-coated Fe3O4 provided in Example 1 of the present invention for the detection of estrogen compounds.

[0025] Figure 6 This is a high performance liquid chromatogram of the magnetic solid phase extraction agent based on carbon-coated Fe3O4 provided in Example 2 of the present invention for the detection of estrogen compounds.

[0026] Figure 7 This is a high performance liquid chromatogram of the magnetic solid phase extraction agent based on carbon-coated Fe3O4 provided in Example 3 of the present invention for the detection of estrogen compounds. DETAILED DESCRIPTION

[0027] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention will be clearly and completely described below in conjunction with the drawings in the present invention. It is obvious that the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. The following embodiments are used to illustrate the present invention, but cannot be used to limit the scope of the present invention.

[0028] In the following examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.

[0029] Example 1 1. Preparation of magnetic solid phase extractant based on carbon-coated Fe3O4.

[0030] First, through a one-step hydrothermal method, a core structure coated with a carbon layer is formed through a hydrothermal process and a dehydration process. Using iron nitrate (nonahydrate) as the iron source and utilizing the reduction characteristics of ethylene glycol at high temperature, ferroferric oxide nanoparticles (referred to as Fe3O4NPs) are prepared. A large number of hydroxyl groups are adsorbed on the surface of Fe3O4NPs. The alcoholic hydroxyl groups on the surface of polyvinyl alcohol will cause polyvinyl alcohol to coat the surface of Fe3O4NPs. As polyvinyl alcohol decomposes under heat, a single carbon layer is formed that coats the surface of Fe3O4 magnetic nanoparticles (Fe3O4@C NPs). The preparation process of Fe3O4@C NPs is as follows: Weigh 2 g of polyvinyl alcohol and add it to 10 mL of deionized water, place it in a 98°C water bath and stir until it is completely dissolved to obtain a polyvinyl alcohol aqueous solution; weigh 2.29 g of ferric nitrate (Fe(NO3)3·9H2O) and dissolve it in 10 mL of deionized water to obtain a ferric nitrate aqueous solution; add the ferric nitrate aqueous solution to the polyvinyl alcohol aqueous solution, then add 60 mL of ethylene glycol solution, mix well, put it into a reactor, place it in a 200°C oven to react for 12 h, and after the reaction is completed, wash it twice with methanol and water in sequence, and dry it to obtain a carbon-coated "core structure", namely Fe3O4@C NPs.

[0031] Secondly, the carbon layer formed on the surface by chemical bonding, in order to solve the problem of chemical modification resistance of the carbon layer, Fe3O4@C NPs are added to the dopamine solution, dopamine self-polymerizes in a weak alkaline environment, and deposits on the surface of Fe3O4@C NPs to form polydopamine, providing a large number of hydroxyl and amino chemical bonding sites. The preparation process of the "core structure" coated with polydopamine modified carbon is as follows: A dopamine aqueous solution with a concentration of 2 mg / mL was prepared, and after oscillation and mixing, Tris buffer was added to adjust the pH of the solution to 8.5, and the solution was oscillated and stirred, and pre-oxidized in the air to obtain a pre-oxidized solution; 40 mg of the magnetic nanoparticles prepared as above was weighed and added to the pre-oxidized solution, and the reaction was stirred at room temperature for 6 h to modify the surface of the magnetic nanoparticles coated with the carbon layer. After the reaction, the magnetic nanoparticles were taken out with a strong magnetic magnet, washed, and dried to obtain a carbon-coated "core structure" with a surface modified with polydopamine.

[0032] Finally, DVA and TAPB were used as monomers, glacial acetic acid was added to initiate the acetal reaction, and the covalent organic framework of poly (DVA-TAPB) was fixed on the surface of Fe3O4 magnetic nanoparticles coated with carbon layer, thus obtaining a magnetic solid phase extractor based on carbon-coated Fe3O4. The preparation process is as follows: Weigh 5 mg of TAPB and 25 mg of DVA and dissolve them in 20 mL of acetonitrile solution, add the magnetic nanoparticles modified with polydopamine prepared above and mix evenly, add glacial acetic acid dropwise, and stir the reaction continuously at room temperature for 12 h. After the reaction, take out the magnetic nanoparticles with a strong magnetic magnet, wash them with methanol, water and methanol in turn, and dry them in an oven at 60°C to obtain a magnetic solid phase extractor based on carbon-coated Fe3O4.

[0033] 2. Characterization of magnetic solid phase extractant based on carbon-coated Fe3O4.

[0034] The Fe3O4 magnetic nanoparticles coated with carbon layer prepared above were examined using a scanning electron microscope. Figure 1 and Figure 2 As shown, the results show that the Fe3O4 magnetic nanoparticles coated with carbon layer have a uniform spherical structure with a particle size of about 10nm and a thin gray boundary on the surface of the magnetic sphere (corresponding to the coated carbon layer structure).

[0035] The magnetic solid phase extractant based on carbon-coated Fe3O4 prepared above was detected using a scanning electron microscope. Figure 3 As shown, the results indicate that a coating structure with uniform thickness (about 8 nm) appears on the surface of the magnetic nanoparticles coated with the carbon layer (corresponding to the poly-DVA-TAPB structure).

[0036] 3. Magnetic solid phase extractor based on carbon-coated Fe3O4 is used for the detection of estrogen-containing compounds.

[0037] Carbon-coated Fe3O4 magnetic solid phase extractor is used in the detection process of estrogen compounds, such as Figure 4 As shown, a carbon-coated Fe3O4 magnetic solid phase extractant is added to a sample solution containing estrogen compounds, and the carbon-coated Fe3O4 magnetic solid phase extractant adsorbs the estrogen compounds on its surface. Under the action of an external magnetic field, the estrogen compounds are separated from the sample solution, and then the estrogen compounds and the carbon-coated Fe3O4 magnetic solid phase extractant are desorbed. The estrogen compounds after desorption are detected by high performance liquid chromatography (HPLC), and the dissociated carbon-coated Fe3O4 magnetic solid phase extractant is recovered and reused under the action of an external magnetic field.

[0038] The magnetic solid phase extractant based on carbon-coated Fe3O4 prepared above was used to perform magnetic solid phase extraction on the sample solution containing estrogen compounds, and then high performance liquid chromatography analysis was performed. The detection process is as follows: the prepared magnetic solid phase extractant based on carbon-coated Fe3O4 was added to the sample solution containing 6 estrogen compounds (estrogen ketone, diethylstilbestrol, estradiol, estriol, diethylstilbestrol, ethinylestradiol), and the estrogen compounds were adsorbed on the surface of the dispersed magnetic solid phase extractant under continuous stirring at room temperature; under the action of an external magnetic field, the estrogen compounds were transferred to a centrifuge tube together with the magnetic solid phase extractant; through solvent ultrasonic desorption and the action of an external magnetic field, the estrogen compounds were separated from the magnetic solid phase extractant, and the estrogen compounds were obtained by a pipette. The estrogen compounds obtained by the above enrichment were analyzed by HPLC.

[0039] HPLC conditions: COSMOSIL C18 column (5 μm inner diameter, 250 mm × 4.6 mm id), 10 mmol / L NaH2PO4 (A) and acetonitrile (B) as mobile phases (total flow rate of 1 mL / min), mobile phase ratio: 0-5 min, 5%-15% B; 5-6 min, 15%-50% B; 6-20 min, 50%-70% B; 20-22 min, 70%-5% B; and 22-30 min, 5% B, the column oven temperature was set to 40 ºC, and the detection wavelength of the UV detector was 230 nm.

[0040] Test results, such as Figure 5 As shown in the figure, A is a chromatogram of the estrogen compound standard after extraction with the magnetic solid phase extractant prepared in this example, and B is a chromatogram of the estrogen compound standard solution without extraction.

[0041] The results showed that the six estrogen compounds (estrone, diethylstilbestrol, estradiol, estriol, diethylstilbestrol, ethinyl estradiol) extracted by magnetic solid phase extractant based on carbon-coated Fe3O4 had good adsorption and enrichment effects.

[0042] Example 2 Weigh 2.5 g of polyvinyl alcohol and add it to 10 mL of deionized water, place it in a 98°C water bath and stir until it is completely dissolved to obtain a polyvinyl alcohol aqueous solution; weigh 2.5 g of ferric nitrate (Fe(NO3)3·9H2O) and dissolve it in 10 mL of deionized water to obtain a ferric nitrate aqueous solution; add the ferric nitrate aqueous solution to the polyvinyl alcohol aqueous solution, then add 65 mL of ethylene glycol solution, mix well, put it into a reactor, place it in a 200°C oven to react for 16 h, and after the reaction is completed, wash it twice with methanol and water in sequence, and dry it to obtain Fe3O4@C NPs.

[0043] A dopamine aqueous solution with a concentration of 2 mg / mL was prepared, and after oscillation and mixing, Tris buffer was added to adjust the pH of the solution to 8.5, and the solution was oscillated and stirred, and pre-oxidized in the air to obtain a pre-oxidized solution; 40 mg of the magnetic nanoparticles prepared as above was weighed and added to the pre-oxidized solution, and the reaction was stirred at room temperature for 4 h to modify the surface of the magnetic nanoparticles coated with the carbon layer. After the reaction, the magnetic nanoparticles were taken out with a strong magnetic magnet, washed, and dried to obtain a carbon-coated "core structure" with a surface modified with polydopamine.

[0044] Weigh 5 mg of TAPB and 30 mg of DVA and dissolve them in 20 mL of acetonitrile solution. Add magnetic nanoparticles modified with polydopamine on the surface and mix well. Add glacial acetic acid dropwise and stir continuously at room temperature for 8 h. After the reaction, take out the magnetic nanoparticles with a strong magnetic magnet, wash them with methanol, water and methanol in turn, and dry them in an oven at 60°C to obtain a magnetic solid phase extractor based on carbon-coated Fe3O4.

[0045] The prepared magnetic solid phase extractant based on carbon-coated Fe3O4 was used to detect estrogen compounds in the sample solution according to the detection method provided in Example 1, such as Figure 6 As shown in the figure, A is a chromatogram of the estrogen compound standard after extraction with the magnetic solid phase extractant prepared in this example, and B is a chromatogram of the estrogen compound standard solution without extraction.

[0046] The results showed that the six estrogen compounds, including estrone, dienystrol, estradiol, estriol, diethylstilbestrol and ethinyl estradiol, had good adsorption and enrichment effects after extraction by magnetic solid phase extractant based on carbon-coated Fe3O4.

[0047] Example 3 Weigh 2 g of polyvinyl alcohol and add it to 10 mL of deionized water, place it in a 98°C water bath and stir until it is completely dissolved to obtain a polyvinyl alcohol aqueous solution; weigh 2.5 g of ferric nitrate (Fe(NO3)3·9H2O) and dissolve it in 10 mL of deionized water to obtain a ferric nitrate aqueous solution; add the ferric nitrate aqueous solution to the polyvinyl alcohol aqueous solution, then add 55 mL of ethylene glycol solution, mix well, put it into a reactor, place it in an oven at 180°C to react for 16 h, and after the reaction is completed, wash it twice with methanol and water in sequence, and dry it to obtain Fe3O4@C NPs.

[0048] A dopamine aqueous solution with a concentration of 1 mg / mL was prepared, and after oscillation and mixing, a Tris buffer solution was added to adjust the pH of the solution to 8.5, and the solution was oscillated and stirred, and pre-oxidized in the air to obtain a pre-oxidized solution; 40 mg of the magnetic nanoparticles prepared as described above were weighed and added to the pre-oxidized solution, and the reaction was stirred at room temperature for 10 h to modify the surface of the magnetic nanoparticles coated with the carbon layer. After the reaction, the magnetic nanoparticles were taken out with a strong magnetic magnet, washed, and dried to obtain a carbon-coated "core structure" with a surface modified with polydopamine.

[0049] Weigh 5 mg of TAPB and 20 mg of DVA and dissolve them in 20 mL of acetonitrile solution, add magnetic nanoparticles modified with polydopamine on the surface and mix well, add glacial acetic acid dropwise, and continue stirring to react at room temperature for 14 h. After the reaction, take out the magnetic nanoparticles with a strong magnetic magnet, wash them with methanol, water, and methanol in turn, and dry them in an oven at 60°C to obtain magnetic nanoparticles modified with covalent organic framework materials on the surface, and obtain a magnetic solid phase extractor based on carbon-coated Fe3O4.

[0050] The prepared magnetic solid phase extractant based on carbon-coated Fe3O4 was used to detect estrogen compounds in the sample solution according to the detection method provided in Example 1, such as Figure 7 As shown in the figure, A is a chromatogram of the estrogen compound standard after extraction with the magnetic solid phase extractant prepared in Example, and B is a chromatogram of the estrogen compound standard solution without extraction.

[0051] The results showed that the six estrogen compounds, including estrone, dienystrol, estradiol, estriol, diethylstilbestrol and ethinyl estradiol, were well adsorbed and enriched after extraction by magnetic solid phase extractant based on carbon-coated Fe3O4.

[0052] The results of Examples 1 to 3 show that the magnetic solid phase extractor based on carbon-coated Fe3O4 provided by the present invention has good adsorption and enrichment effects on estrogen compounds and can be used for the enrichment and determination of such substances in samples such as food and plasma.

[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A magnetic solid phase extractor based on carbon-coated Fe3O4, characterized in that: It comprises a Fe3O4 core, a carbon layer and a covalent organic framework, wherein the carbon layer is coated on the surface of the Fe3O4 core, and the covalent organic framework is fixed on the carbon layer; Wherein, the surface of the carbon layer is modified with hydroxyl and amino chemical bonding sites.

2. The magnetic solid phase extractant based on carbon-coated Fe3O4 according to claim 1, characterized in that: The Fe3O4 core is Fe3O4 magnetic nanoparticles.

3. The magnetic solid phase extractant based on carbon-coated Fe3O4 according to claim 1, characterized in that The hydroxyl and amino chemical bonding sites for modifying the surface of the carbon layer are provided by the polydopamine modified on the surface of the carbon layer.

4. The magnetic solid phase extractant based on carbon-coated Fe3O4 according to claim 1, characterized in that The covalent organic skeleton is an organic skeleton formed by covalently connecting 2,5-divinylterephthalaldehyde and 1,3,5-tris(4-aminophenyl)benzene.

5. A method for preparing a magnetic solid phase extractant, characterized in that: The method for preparing a magnetic solid phase extractor based on carbon-coated Fe3O4 as claimed in any one of claims 1 to 4 comprises the following steps: S100, using a polyvinyl alcohol solution and an iron salt solution to prepare Fe3O4 magnetic nanoparticles with a carbon layer coated on the surface; S200, using a dopamine solution to modify Fe3O4 magnetic nanoparticles with a carbon layer on the surface to obtain magnetic nanoparticles with polydopamine modified on the surface; S300, placing magnetic nanoparticles modified with polydopamine on the surface into an organic solution of 2,5-divinylterephthalaldehyde and 1,3,5-tri(4-aminophenyl)benzene, and preparing a magnetic solid phase extractor based on carbon-coated Fe3O4 through an acetal reaction.

6. The method for preparing a magnetic solid phase extractant according to claim 5, characterized in that: In step S100, the mass concentration of the polyvinyl alcohol solution is 0.2 g / mL to 0.25 g / mL.

7. The method for preparing a magnetic solid phase extractant according to claim 5, characterized in that: In step S100, the mass concentration ratio of the polyvinyl alcohol solution to the iron salt solution is 1:1 to 1:1.

25.

8. The method for preparing a magnetic solid phase extractant according to claim 5, characterized in that: In step S200, the concentration of the dopamine solution is 1 mg / mL to 2 mg / mL.

9. The method for preparing a magnetic solid phase extractant according to claim 5, characterized in that: In step S300, the mass ratio of 2,5-divinylterephthalaldehyde to 1,3,5-tris(4-aminophenyl)benzene is 4:1 to 6:

1.

10. An application of a magnetic solid phase extractor, characterized in that: The magnetic solid phase extractant is the magnetic solid phase extractant based on carbon-coated Fe3O4 as described in any one of claims 1 to 4, and the application includes enrichment and analysis of estrogen compounds.